Correction to: Probabilistic maps on bistable vibration energy harvesters (Nonlinear Dynamics, (2023), 10.1007/s11071-023-08864-2) - Norenberg, João Pedro [UNESP]; Cunha, Americo; da Silva, Samuel [UNESP]; Varoto, Paulo Sergio (Springer Nature, 2023)
The article was originally published with formatting errors tied to Code Availability and Conflict of Interest sections. The article has been updated to present the article as it was intended. The original article has been corrected.